Estimation of productivity, protein percentage in grain and hoodness of spring barley varieties in the conditions of the middle Volga region - E. N. Shabolkina; S. N. Shevchenko; A. A. Bisharev; I. A. Kalyakulina; N. V. Anisimkina (Зерновое хозяйство России)
Taking into account the main purposes of barley use (food, feed, brewing), one of the main tasks is to develop highly productive and high-quality varieties with specified grain protein parameters that meet Russian and international standards for targeted use, since the requirements for protein percentage in grain are different. The purpose of the current study was to estimate the productivity and protein percentage in grain of spring barley varieties, to identify correlations between productivity, protein percentage and grain hoodness. There has been established that, depending on the weather conditions of the vegetation period, the yield decrease of spring barley grain from 3.96 t/ha to 1.56 t/ha during the years of study was due to a decrease in productive tillering, grain weight per head, and number of grains per head. According to the results of the correlation analysis, barley productivity did not depend on 1000-grain weight. On average, in 2018–2022, the largest productivity was formed by the barley varieties ‘Kholzan’ with 2.93 t/ha and ‘Sarych’ with 2.88 t/ha. There has been identified a group of such varieties with an increased amount of protein, regardless of the weather conditions of the vegetation period as ‘Lun’, ‘Prairiya’, ‘Bezenchuksky 2’, ‘Kholzan’, ‘Orlan’, with the maximum protein percentage of 14.5 % formed by the variety ‘Lun’. These spring barley varieties are suitable for food (cereals) and feed purposes. There has been established that the maximum percentage of protein substances was formed in very dry years (17.0 % by the variety ‘Lun’). There has been found a significant inverse correlation between grain productivity and protein content only in years with contrasting weather conditions, namely in the extremely dry 2021 (–0.65*) and in the favorable for plant growth and development 2022 (–0.60*). There was seen a similar situation between protein percentage and grain hoodness with –0.66* in 2021 and –0.73** in 2022. On average, over the years of study, there was no significant correlation between these indicators, which demonstrates the possibility of breeding highly productive spring barley varieties with protein percentage in grain at the level of existing standards.